Non-functional biomimicry: utilizing natural patterns in order to provoke attention responses. Issue 1 (3rd April 2018) - Young, Bryan G.; Wodehouse, Andrew
Abstract: Natural reoccurring patterns arise from chaos and are prevalent throughout nature. The formation of these patterns is controlled by, or produces, underlying geometrical structures. Biomimicry is the study of nature's structure, processes and systems, as models and solutions for design challenges and is being widely utilized in order to address many issues of contemporary engineering. Many academics now believe that esthetics stem from pattern recognition, consequently, esthetic preference may be a result of individuals recognizing, and interacting with, natural patterns. The goal of this research was to investigate the impact of specific naturally occurring pattern types (spiral, branching, and fractal patterns) on user behavior; investigating the potential of such patterns to control and influence how individuals interact with their surrounding environment. The results showed that the underlying geometry of natural patterns has the potential to induce attention responses to a statistically significant level.